A influência da maturidade do Sistemas de Gestão da Qualidade no desempenho internacional: uma análise de empresas do setor metalmecânico da Serra Gaúcha - Souza, Bruna Neu (My University, 2018)
The current literature does not talk about the relation between quality management system and international performance. In fact, there is a long list of publications that analyze the relation between quality management systems and organizational performance, but when it comes to international performance, results are scarce and most studies that contain these terms in their titles, abstracts and keywords do not go so far as to analyze this relation. Given this gap, the present study aimed to analyze the relation between quality management system and international performance in a sample of companies from the Serra Gaúcha region (southern Brazil). To do so, both the maturity of the company's quality management system, including ISO 9001 certification, and its international performance were considered, being selected the most cited indicators in the literature. The data were collected through a survey sent to a sample of xxx companies of the metallurgical sectors of the studied region and analyzed through procedures of descriptive statistics, hypothesis tests and correlations analysis. The results showed that (i) the sample companies have maturity levels in quality management systems higher than the center point of the scale; (ii) in terms of international performance, the percentage of exports in total revenues varies from 0% to 80%, obtaining a percentage of 57% of companies with more than 1/3 of the annual revenue composed of exports; (iii) there are statistically significant differences in the maturity of the quality management system and international performance among companies of different sizes; (iv) the maturity of the quality management system did not show a statistically significant relation. These results allow us to conclude that the maturity of the quality management system may not influence international performance.(sic)
A atual literatura pouco fala sobre a relação entre sistemas de gestão da qualidade e desempenho internacional de empresas. De fato, é longa a lista de publicações que analisam a relação entre sistemas de gestão da qualidade e desempenho organizacional, mas, quando se trata de desempenho internacional, os resultados são escassos e a maioria dos estudos que contêm esses termos em seus títulos, resumos e palavras-chave não chegam a analisar essa relação. Dada essa lacuna, o presente estudo analisou a relação entre sistema de gestão da qualidade e desempenho internacional em uma amostra de empresas da Serra Gaúcha (sul do Brasil). Para tanto, foram considerados tanto a maturidade do sistema de gestão da qualidade das empresas, incluindo a certificação ou não pela norma ISO 9001, quanto seu desempenho internacional, sendo selecionados os indicadores mais citados na literatura. Os dados foram coletados por meio de uma survey enviada a uma amostra de 2000 empresas do setor metalmecânico da região estudada e analisados mediante procedimentos de estatística descritiva, testes de hipótese e análise de correlação. Os resultados evidenciaram que (i) as empresas da amostra possuem níveis de maturidade em sistemas de gestão da qualidade maiores que o ponto central da escala; (ii) tratando- se de desempenho internacional, o percentual de exportações no faturamento total varia de 0% a 80%, obtendo-se um percentual de 57% de empresas com mais de 1/3 da receita anual composta de exportações ; (iii) há diferenças estatisticamente significantes de maturidade do sistema de gestão da qualidade e desempenho internacional entre empresas de diferentes portes; (iv) a maturidade do sistema de gestão da qualidade não se verificou uma relação estatisticamente significante. Esses resultados permitem concluir que a maturidade do sistema de gestão da qualidade pode não influir no desempenho internacional.(sic)
Keywords: ISO 9001; Gestão da qualidade total; Indústria metal-mecânica - Serra, Região (RS)